DAYA TARIK WISATA DI DANAU ALI KECAMATAN MANDAU KABUPATEN BENGKALIS PROVINSI RIAU - Prayoga, Dimas; Yulia, Nur Arini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to explore and examine in depth the tourism attractions of Danau Ali, located in Mandau District, Bengkalis Regency, Riau Province. Danau Ali is a man-made tourism destination that has gained popularity among the local community due to its serene atmosphere, making it suitable for relaxing activities. This research focuses on three main components of tourist attraction: what to see (visual attractions), what to do (activities that tourists can engage in), and what to buy (products or souvenirs available for purchase). Additionally, the study also analyzes the role of the site management, the availability of supporting facilities, visitor participation, and the challenges faced in managing the tourist area. A descriptive qualitative approach was employed in this study, with data collected through field observations, in-depth interviews with various sources, and documentation. Data analysis followed the interactive model by Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that Danau Ali's main strength lies in its appealing artificial landscape and the variety of activities available to visitors, such as fishing, relaxing, jogging, and participating in community events. However, the shopping aspect or what to buy has not been fully developed due to the lack of souvenir shops or local specialty products. The management faces several challenges, including limited operational funds, inadequate maintenance of facilities, and low visitor awareness regarding cleanliness. Therefore, improvements in management, greater support from various stakeholders, and increased visitor education are needed to ensure the sustainability and quality of Danau Ali as a tourist destination. Keywords: Danau Ali tourism, tourist attraction, recreational activities, tourism management